Management of the Internal Problems of NATO Countries: Threat to European Security - Jerzy BĘDŹMIROWSKI; Miłosz GAC (Communications of International Proceedings, 2020)
This article points to the internal problem of nation states and the Warsaw Pact at the turn of the 1950s and 1920s. It also indicates the threats to European security. Events threatening destabilization in the Warsaw Pact countries took place in Poland (1967-1968) and Czechoslovakia in 1968. The events in Poland had a background in the Middle East events.
Keywords: Management; Internal Problems; NATO; Warsaw Pact; European Security.